The Influence of Competence and Motivation Work on Employee Performance at The Provincial Food Crops Service West Java - Mutmainah, Islahul; Komar Priatna, Deden; Sukmayana, Dodi (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The Office of Food Crops of West Java Province as one of the Regional Government Organizations (OPD) of the West Java Province, which has the authority for the Management of Food Crop Agriculture. However, on the other hand, the obstacle is not achieving realization of the output produced is not in accordance with the plan that has been previously set. The low performance of employees of the Food Crop Service of West Java Province is allegedly due to low competence and motivation. The purpose of this study was to find out the effect of competence and work motivation on employee performance, both simultaneously and partially, and discussed descriptively. The method used is descriptive survey method and explanatory survey. The type of investigation in this study is causality. The unit of analysis of staff of the Food Crop Service in West Java Province with a sample (n) of 50 employees. Time horizon in this study is cross sectional and the analytical method used is frequency distribution and path analysis. The findings of this study are that employee competencies are generally assessed on good criteria; Work motivation given to employees is inadequate; employee performance has high and very high performance Work motivation and competency together influence the performance of the staff of the Food Crop Service in West Java Province. But partially dominant work motivation influences employee performance rather than competence.